Cadmium toxicity affects chlorophyll a and b content, antioxidant enzyme activities and mineral nutrient accumulation in strawberry - Muradoglu, Ferhad; Gundogdu, Muttalip; Ercisli, Sezai; Encu, Tarik; Balta, Fikri; Jaafar, Hawa ZE; Zia-Ul-Haq, Muhammad (Biological research, 2015)
Cadmium (Cd) is well known as one of the most toxic metals affecting the environment and can severely restrict plant growth and development. In this study, Cd toxicities were studied in strawberry cv. Camarosa using pot experiment. Chlorophyll and malondialdehyde (MDA) contents, catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX) activities and mineral nutrient concentrations were investigated in both roots and leaves of strawberry plant after exposure Cd. Cd content in both roots and leaves was increased with the application of increasing concentrations of Cd. We found higher Cd concentration in roots rather than in leaves. Chlorophyll a and b was decreased in leaves but MDA significantly increased under increased Cd concentration treatments in both roots and leaves. SOD and CAT activities was also increased with the increase Cd concentrations. K, Mn and Mg concentrations were found higher in leaves than roots under Cd stress. In general, increased Cd treatments increased K, Mg, Fe, Ca, Cu and Zn concentration in both roots and leaves. Excessive Cd treatments reduced chlorophyll contents, increased antioxidant enzyme activities and changes in plant nutrition concentrations in both roots and leaves. The results presented in this work suggested that Cd treatments have negative effect on chlorophyll content and nearly decreased 30% of plant growth in strawberry. Strawberry roots accumulated higher Cd than leaves. We found that MDA and antioxidant enzyme (CAT, SOD and APX) contents may have considered a good indicator in determining Cd tolerance in strawberry plant.